Efficient blue electroluminescence with an external quantum efficiency of 9.20% and CIEy < 0.08 without excimer emission. Issue 42 (1st July 2020) - Jayabharathi, Jayaraman; Sivaraj, Sekar; Thanikachalam, Venugopal; Seransenguttuvan, Balu
Abstract : Aromatically substituted phenanthroimidazoles at the C6 and C9 positions enhanced the thermal, photochemical and electroluminescence properties due to extension of conjugation. Abstract : Aromatically substituted phenanthroimidazoles at the C6 and C9 positions enhanced the thermal, photochemical and electroluminescence properties due to extension of conjugation. These new materials exhibit good photophysical properties with high thermal stability, good film-forming property and high luminous efficiency. The electroluminescence performances of C6 and C9 modified phenanthroimidazoles as host emitters were evaluated as well as the dopant in the fabricated devices. Among the non-doped devices, pyrene substituted PPI-Py or PPICN-Py based devices show maximum efficiency: PPI-Py/PPICN-Py: η c (cd A −1 ) – 9.20/9.98; η p (lm W −1 ) – 8.50/9.16; η ex (%) – 5.56/5.80. The doped OLEDs, m -MTDATA/TAPC:PPI-Cz (4.81/4.85%), m -MTDATA/TAPC:PPICN-Cz (5.23/5.26%), m -MTDATA/TAPC:PPI-An (5.01/5.04%), m -MTDATA/TAPC:PPICN-An (5.25/5.28%), m -MTDATA/TAPC:PPI-Py (5.61/5.65%) and m -MTDATA/TAPC:PPICN-Py (5.76/5.78%) show improved device efficiencies compared to non-doped devices. Designing C6/C9 modified phenanthrimidazole fluorophores is an efficient strategy for constructing highly efficient OLEDs.